Peninjauan Mutu Beton Ready Mix pada Baching Plant-Surabaya - Rizqi Dwi Nanda; Febriyanti Milo; Intan Rizqi Nalindri; Galuh Windu Anjasari; Dika Ayu Safitri (International Forum of Researchers and Lecturers, 2024)
Quality control review of concrete at PT. Merak Jaya Beton is important to ensure that the work carried out meets quality standards and is implemented according to existing procedures. PT. Merak Jaya Beton is one of the companies in Indonesia that produces precast concrete. At PT. Merak Jaya Beton, quality is highly regarded from trials before being taken to projects (trial mix and F’c)to construction projects (Slump tests), checking the proportions of mixtures and uniformity of basic materials at the batching plant, to hammer test checks. The process of selecting the right concrete materials can determine the amount or quantity of dependency on materials considering the quality requirements of the concrete used. Several specifications of ready-mix concrete are produced to meet the specifications demands from clients. Meanwhile, for material quantity planning based on the production volume to be implemented, it includes material needs, ordering cycles, and the amount of orders. In concrete mixtures, there are materials added during the Mixing process (admixtures), this is aimed to alter the properties of concrete to make it more suitable and cost-effective.